The effectiveness of Google Forms in assessing and evaluating online learning outcomes: Meta-analysis study - Andi Abdurrahman Manggaberani; Andi Muhammad Darlis (Publikasi Indonesia, 2024)
The use of Google Forms as a learning tool in certain subjects is massively used in several schools because of its efficiency. This research aims to identify, classify, and observe literature, synthesize several studies that have been carried out, analyze the contributions that have been made, and propose related research updates. This study uses a methodology supported by a research approach, documentation, and procedural models from systematic literature review and data analysis using quantitative and qualitative descriptive analysis techniques. The results of this study show the effectiveness of Google Forms on the assessment and eval_uation of student learning outcomes, which from the table has proven that there are 36 studies (90%) that agree that the use of Google Forms has a positive or effective influence on success in assessing and eval_uating learning outcomes. This conclusion underscores the importance of digital marketing in the modern technology era. Digital marketing allows businesses to effectively reach global audiences through social media, SEO, and content. In this study, it was seen that a good digital strategy can increase brand awareness and customer loyalty. By utilizing proper data analysis, companies can optimize their digital marketing campaigns for better results. In conclusion, digital marketing is the key to winning the competition in an increasingly competitive market.